Variations in Nonlinear Gamma Wave Dynamics During the Resolution of a Test of Attention After the Application of Physical Exercise [Variaciones de Las Dinámicas No Lineales de Las Ondas Gamma Durante la Resolución de Una Prueba de Atención Tras la Aplicación de Ejercicio Físico] - Diaz-Munoz, H (Federacion Espanola de Docentes de Educacion Fisica, 2019)
Introduction: Electroencephalography is a useful tool for studying the association between motor activities and cognitive functions. Material and method: the aim of this research was to study the effects of 30 minutes of aerobic exercise on gamma brain waves during the resolution of a selective attention test. The sample consisted of 12 university students (7 experimental and 5 control). The recording of brain activity was performed with brain-interface device Emotiv Epoc® during the resolution of the Toulouse-Piéron selective attention test conducted before and after 30 minutes of aerobic physical exercise. Results: variations in Hurst indices are observed in the right and left prefrontal regions, in addition to the left temporal region after physical exercise. The correlations of the frontal, temporal and occipital regions increased or decreased after the intervention, although the scores on the test increased in all of them. Conclusions: it is not possible to associate a single brain function with the improvement in the results of a cognitive test after physical exercise, as there exists an enormous variability of brain strategies for solving a cognitive problem. © Federación Española de Asociaciones de Docentes de Educación Física (FEADEF) ISSN: Edición impresa: 1579-1726. Edición Web: 1988-2041 (www.retos.org)